Peran Kelompok Wanita Tani (KWT) Terhadap Peningkatan Pendapatan Keluarga (Studi Kasus KWT Muda Mandiri Desa Dutohe Barat Kecamatan Kabila Kabupaten Bone Bolango) - Manto, Rizky Amalia; Indriani, Ria; Saleh, Yanti (AGRI-SOSIOEKONOMI, 2023)
The aims of this study were 1) to find out the income of the Independent Young Women Farmers Group (KWT) in West Dutohe Village, Kabila District, Bone Bolango Regency, 2) To know and analyze the role of the Independent Young Women Farmers Group in increasing family income in West Dutohe Village, Kabila District, Bone Bolango Regency, by using the Survey Method. This research was conducted in Dutohe Barat Village, Kabila District, Bone Bolango Regency in October to December 2022. The data analysis used was income analysis, value added analysis, descriptive analysis and spearman rank correlation analysis to explain the role of Independent Young Women Farmers Groups in increasing income. family in Dutohe Barat, Kabila District, Bone Bolango Regency. The results showed that: 1) the average income of the Independent Young Women Farmers Group in Dutohe Barat Village, Kabila District, Bone Bolango Regency was Rp. 5,205,033.34/month. The added value obtained from village coconut oil processing was Rp. 26,000/kg with an added value ratio of 74.29%. 2) the test results show that the average respondent's assessment of the role of women farming groups as a whole is 80.135% which is categorized as good and the Role of Independent Young Women Farming Groups in Dutohe Barat Village, Kabila District, Bone Bolango Regency has a positive relationship or there is a real relationship (significant) to an increase in family income.